Seasonality in National Stock Exchange Indices and Pharmaceutical Industry - Selvarani, M.; Lakshmi Shree, M. (Indian Journal of Finance, 2009)
Seasonality is a repeatable tendency of a financial instrument to move in relation to a particular influencing factor. That factor could be the time of year, the year of a decade, changes in interest rates, inflation, energy prices, etc. We focus on stock price action and seasonal cycles derived from the time of the calendar year. Seasonal cycles do not cause prices to move a certain way. They simply reflect a measure of tendency. Seasonality is based on both fundamental and technical elements. The present study examines empirically the day of the week effect and Month of the year effect anomaly in the NSE Indices and selected pharmaceutical companies for the period from 2002 to 2007. A nonparametric test Kruskal-Wallis is used to test mean returns are equal across the days of the week. The findings on the mean returns in NSE indices and Pharmaceutical companies could be useful in designing trading strategies and drawing investment decisions. After the introduction of the rolling settlement, Friday has become significant. This also indicates that Fridays, being the last days of the weeks have become significant after rolling settlement. Mondays were found to have higher standard deviations followed by Fridays. The existence of market inefficiency is clear. The market inefficiency still exists and market is yet to price the risk appropriately.